Culture Directed Antibiotic Prophylaxis Reduces Post‐Prostate Biopsy Infectious Complications in the Community: A "How‐to" for Urologists in the Trenches. Issue 4 (July 2015) - Farrell, James; Salter, Carolyn; Cullen, Jennifer; Mordkin, Robert; Joel, Andrew
Abstract : Introduction: : The rate of post‐prostate biopsy infection is increasing. We noted this trend in our practice and began using prebiopsy rectal swab cultures to direct antibiotic prophylaxis. Clinical investigation has shown that culture directed antibiotic prophylaxis is effective. We report our methods and results as validation that culture directed antibiotic prophylaxis works in the community. Methods: : We retrospectively reviewed the charts of 686 consecutive patients who underwent transrectal prostate biopsy from March 2010 to April 2013. The electronic medical record was queried for the antibiotic prophylaxis used, rectal swab culture, post‐biopsy infection, culture data and post‐biopsy hospitalization if applicable. Prebiopsy rectal swab was incorporated into our practice in May 2012. Each patient received 3 days of fluoroquinolone prophylaxis or culture directed antibiotic prophylaxis. If antibiotic resistance to standard fluoroquinolone prophylaxis was identified, antibiotic prophylaxis was adjusted appropriately. Results: : Of 543 patients who received standard fluoroquinolone prophylaxis 17 (3.1%) had infectious complications. Eight patients were hospitalized for post‐biopsy sepsis and 4 received outpatient treatment for urinary tract infection. A total of 143 patients underwent prebiopsy rectal swabs and received culture directed antibiotic prophylaxis. Compared to standard antibiotic prophylaxis no patient treated with culture directed antibiotic prophylaxis after a rectal swab had infectious complications (p = 0.03). However, 19.5% of the patients in this group had resistant bacteria requiring alternative antibiotic prophylaxis. Conclusions: : A prebiopsy rectal swab to direct antibiotic prophylaxis decreased post‐biopsy infectious complications in the community setting. The strategy is simple and it improves patient safety.